Narcissistic Leaders and Their Victims: Followers Low on Self-Esteem and Low on Core Self-Evaluations Suffer Most - Nevicka, Barbara; De Hoogh, Annebel H. B.; Den Hartog, Deanne N.; Belschak, Frank D. (Frontiers in Psychology, 2018)
Narcissistic leaders are self-absorbed and hold beliefs of entitlement and superiority. Their aggressive tendencies in the face of criticism and inclinations to validate their self-worth by derogating others may lead others to perceive them as being abusive. Here, we test the relationship between leader narcissism and followers' perceptions of abusive supervision. Drawing upon research related to the behavioral plasticity hypothesis, we propose that followers with low self-esteem will perceive narcissistic leaders as more abusive than those with high self-esteem. Followers low on self-esteem are more insecure, more in need of approval from their supervisor and are more likely to interpret the haughty, derogatory attitude of narcissistic leaders as abusive. Such followers also make for 'easier targets' and thus may actually suffer more abusive behavior from their narcissistic leaders. In a first multi-source study of 85 leaders and 128 followers, we found support for the moderating role of follower self-esteem in the relationship between leader narcissism and perceived abusive supervision: Narcissistic leaders were rated as more abusive by followers who were low on self-esteem, but not those higher on self-esteem. In a second multi-source field study among 177 leader-follower dyads, we tested a moderated mediation model and showed that this finding also holds for the broader concept of follower core self-evaluations as a moderator. Abusive supervision, in turn, was related to lower follower performance and followers experiencing more burnout symptoms. Thus, followers low on self-esteem or low on core self-evaluations seem to suffer most from narcissistic leaders as they perceive them to be abusive and, in turn, these followers show reduced performance and more burnout symptoms when working for such leaders. This research thus identifies an important moderator that might help reconcile previous inconsistent findings regarding perceptions of narcissistic leaders.